Spare Parts: A Public Lecture Series - K-State First (Kansas State University, K-State First., 2016)
This poster advertises two events. The first event is Coming Out of the Shadows: A panel discussion. A panel of students share their experiences and thoughts about being an undocumented student at Kansas State University. The second event, A Conversation with Fredi Lajvardi. Fredi Lajvardi is a practicing high school teacher, nationally recognized STEM educator, and subject of the documentary “Underwater Dreams” and “Spare Parts”. He will talk about his experience teaching at Carl Hayden Community High School.
Citation: K-State First (2016). Spare Parts: A Public Lecture Series [Flier]. Manhattan, Kansas: K-State First.
Keywords: Spare Parts; Common reading program; Promotional materials; Promotional materials